2016
DOI: 10.1158/1535-7163.mct-15-0486
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Inhibition Blocks Multiple Myeloma Cell Growth through Upregulation of Epithelial Tumor Suppressor Genes

Abstract: Multiple myeloma is a plasma cell malignancy characterized by marked heterogeneous genomic instability including frequent genetic alterations in epigenetic enzymes. In particular, the histone methyltransferase Enhancer of Zeste Homolog 2 (EZH2) is overexpressed in multiple myeloma. EZH2 is the catalytic component of the polycomb repressive complex 2 (PRC2), a master transcriptional regulator of differentiation. EZH2 catalyzes methylation of lysine 27 on histone H3 and its deregulation in cancer has been report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 51 publications
5
56
0
Order By: Relevance
“…We recently identified a common H3K27me3-marked chromatin profile mediated by EZH2 among MM patients that correlates to gene silencing in advanced stages of the disease and to poor clinical outcome [18, 23]. Furthermore, we and others have demonstrated that EZH2 provides a potential therapeutic target in MM by using highly selective inhibitors of EZH2 in vitro [23, 24] and in vivo [24]. Here we further investigated the anti-myeloma effects mediated by pharmacological inhibition of EZH2 by focusing on downregulated genes in MM and the molecular mechanisms underlying this observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently identified a common H3K27me3-marked chromatin profile mediated by EZH2 among MM patients that correlates to gene silencing in advanced stages of the disease and to poor clinical outcome [18, 23]. Furthermore, we and others have demonstrated that EZH2 provides a potential therapeutic target in MM by using highly selective inhibitors of EZH2 in vitro [23, 24] and in vivo [24]. Here we further investigated the anti-myeloma effects mediated by pharmacological inhibition of EZH2 by focusing on downregulated genes in MM and the molecular mechanisms underlying this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we could show that genes commonly silenced in MM, as compared with normal plasma cells, are PRC2 targets and that the histone methylation of these targets correlated with gene repression in advanced MM stages and in patients with poor survival [18, 23]. Moreover, we and others demonstrated that pharmacological inhibition of EZH2 using small specific chemical inhibitors is a potentially interesting therapeutic strategy in MM [23, 24]. Collectively, these data suggest an important role for EZH2 and H3K27me3 in MM pathogenesis and highlight EZH2 as a promising therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…In MM, EZH2 expressions are induced on interleukin 6 (IL-6) stimulation in IL6-dependent cell lines, while constitutively expresses in IL-6-independent cell lines; and the expression of EZH2 is correlative with MM cells’ proliferation, which is abrogated by siRNA treatment [21]. In addition, pharmaceutical inhibition of EZH2 by EPZ6438 blocks the growth of MM cells [42]. In agreement with these results, we found that GSK126 also repressed the growth of several MM cell lines, with IC 50 ranging from 12.6 μM to 17.4 μM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KDM6A loss in MM led to repression of a specific gene set that can be re-expressed by EZH2 inhibition, leading to cell death (65). EZH2 inhibitor sensitivity in MM has been attributed to downregulation of MM oncogenes such as c-MYC, XBP-1, IRF-4, PRDM1 (64), and upregulation of epithelial tumor suppressor genes like CDH1 (63). …”
Section: Histone Methylation Mediated By Set Domain Methyltransferasesmentioning
confidence: 99%